Improving Public Service Delivery through E-Government Innovation in Regional Bureaucracy: A Case Study of Disdukcapil Sleman - Sa’adih, Sa’adih; Fahmi, Ade; Perdanaputra, Decky (Universitas Sang Bumi Ruwa Jurai, 2021)
This study analyzes the implementation of e-Government in improving the quality of public services at the Department of Population and Civil Registration (Disdukcapil) in Sleman Regency. Utilizing qualitative descriptive methods with data collected through interviews, documentation, and literature studies prior to 2021, the research finds that innovations such as the